2012
DOI: 10.1021/ml300056y
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactones Inhibit N-acylethanolamine Acid Amidase by S-Acylation of the Catalytic N-Terminal Cysteine

Abstract: ABSTRACT:The cysteine amidase N-acylethanolamine acid amidase (NAAA) is a member of the N-terminal nucleophile class of enzymes and a potential target for anti-inflammatory drugs. We investigated the mechanism of inhibition of human NAAA by substituted β-lactones. We characterized pharmacologically a representative member of this class, ARN077, and showed, using high-resolution liquid chromatography−tandem mass spectrometry, that this compound forms a thioester bond with the N-terminal catalytic cysteine in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 31 publications
8
48
0
Order By: Relevance
“…131 Mass spectrometry studies supposed that the nucleophilic thiol group of the Cys131 of rat NAAA interact the carbonyl of β-lactone group to form an acyl-NAAA intermediate. 7,131,132 The β-lactone group has been shown to react readily with nucleophiles, and can be rapidly hydrolyzed in aqueous solution. In fact, most amide-based β-lactone derivatives were rapidly hydrolyzed in aqueous buffer at pH 7.4 with half-lives of less than 20 minutes, whereas the β-substituted methyl group endowed the β-lactone derivatives with improved stability (half-life > 70 min).…”
Section: β-Lactonesmentioning
confidence: 99%
See 1 more Smart Citation
“…131 Mass spectrometry studies supposed that the nucleophilic thiol group of the Cys131 of rat NAAA interact the carbonyl of β-lactone group to form an acyl-NAAA intermediate. 7,131,132 The β-lactone group has been shown to react readily with nucleophiles, and can be rapidly hydrolyzed in aqueous solution. In fact, most amide-based β-lactone derivatives were rapidly hydrolyzed in aqueous buffer at pH 7.4 with half-lives of less than 20 minutes, whereas the β-substituted methyl group endowed the β-lactone derivatives with improved stability (half-life > 70 min).…”
Section: β-Lactonesmentioning
confidence: 99%
“…135 Compound 111 rapidly, non-competitively, covalently and reversibly combined with rat NAAA, whereas the inhibition of human NAAA was only partially reversible. 132 The binding mechanism studies indicated that the thiol group of the active cysteine (Cys131 for rat NAAA, Cys126 for human NAAA)…”
Section: β-Lactonesmentioning
confidence: 99%
“…Heck293-WT cells, Hek293 cells overexpressing hAC1 (Hek293-hAC1) [19], and Hek293 cells overexpressing human NAAA (Hek293-hNAAA) [20] were plated in 150-mm dishes (5 Â 10 6 cells/ dish) and cultured in complete DMEM containing 10% fetal bovine serum, 2 mM L-glutamine, and antibiotics (100 U/ml penicillin and streptomycin) at 37 C and 5% CO 2 . Cell media were collected 48 h after incubation.…”
Section: Cell Culturesmentioning
confidence: 99%
“…In this regard, it should be pointed out that a hopping exercise aimed at identifying completely novel chemical scaffolds was outside the scope of the present 3D QSAR study. Furthermore, given the covalent nature of the interaction established by these compounds with the enzyme, 36 fair activity predictions based on structure can only be limited to compounds sharing the same mechanism of covalent inhibition. However, each new compound displayed a new structural feature, which incrementally expanded our knowledge of the shape of the pocket, particularly relevant also in light of the lack of a NAAA crystal structure to be utilized in structure-based studies.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…32 Structure−activity relationship (SAR) studies of α-amino-β-lactone derivatives, as carbamic acid esters, investigated the effects on NAAA inhibition of side chain modifications and the stereochemical requirements of the introduction of a β-substitution. 33−35 These works led to the identification of compounds that were highly potent at inhibiting both rat and human NAAA, such as β-lactones 1 (ARN077) 33,34,36 and 2…”
Section: ■ Introductionmentioning
confidence: 99%